Dual functionalized hyaluronic acid micelles loading paclitaxel for the therapy of breast cancer - Liu, Zhanbiao; Chen, Xuejun; Jin, Qian; Li, Min; Zhu, Siqing; Zhang, Yi; Zhi, Defu; Zhao, Yinan; Li, Liqin; Zhang, Shubiao (Frontiers in Bioengineering and Biotechnology, 2023)
Although many carriers for the delivery of chemotherapeutic drugs have been investigated, the disadvantages of passive targeting and uncontrolled drug release limit their utility. Herein, hyaluronic acid (HA) was hydrophobically modified to serve as a carrier for binding to cluster determinant 44 (CD44) overexpressed on tumor cell surfaces. Specifically, after deacetylation, HA was grafted to dodecylamine or tetradecylamine to afford amphiphilic zwitterionic polymer micelles, designated dHAD and dHAT, respectively, for the delivery of paclitaxel (PTX). The micelles were negatively charged at pH 7.4 and positively charged at pH 5.6, and this pH sensitivity facilitated PTX release under acidic conditions.The cell uptake efficiencies of the dHAD-PTX and dHAT-PTX micelles by MCF-7 cells after 4 h of incubation were 96.9% and 95.4%, respectively, and their affinities for CD44 were twice that of HA. Furthermore, the micelles markedly inhibited tumor growth both in vitro and in vivo, with IC 50 values of 1.943 μg/mL for dHAD-PTX and 1.874 μg/mL for dHAT-PTX for MCF-7 cells; the tumor inhibition rate of dHAD-PTX (92.96%) was higher than that of dHAT-PTX (78.65%). Importantly, dHAD and dHAT micelles showed negligible systemic toxicity. Our findings suggest that these micelles are promising delivery vehicles for antitumor drugs.